2022
DOI: 10.3389/fimmu.2022.923582
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitogenic T Cells in Large Vessel Vasculitis

Abstract: Vasculitis is an autoimmune disease of unknown etiology that causes inflammation of the blood vessels. Large vessel vasculitis is classified as either giant cell arteritis (GCA), which occurs exclusively in the elderly, or Takayasu arteritis (TAK), which mainly affects young women. Various cell types are involved in the pathogenesis of large vessel vasculitis. Among these, dendritic cells located between the adventitia and the media initiate the inflammatory cascade as antigen-presenting cells, followed by act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Recently, low-dose IL-2 therapy has been expected to be effective against autoimmune diseases such as SLE because it can expand CD4 + Tregs [ 33 , 43 ]. The anti-IL-6 inhibitor tocilizumab can also restore the number and functions of CD4 + Tregs [ 17 , 44 , 45 ]; however, these effects on CD8 + Tregs are unknown [ 46 ]. Several attempts to expand CD8 + Tregs using probiotics or by in vitro or in vivo procedures are under investigation to treat autoimmunity [ 20 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, low-dose IL-2 therapy has been expected to be effective against autoimmune diseases such as SLE because it can expand CD4 + Tregs [ 33 , 43 ]. The anti-IL-6 inhibitor tocilizumab can also restore the number and functions of CD4 + Tregs [ 17 , 44 , 45 ]; however, these effects on CD8 + Tregs are unknown [ 46 ]. Several attempts to expand CD8 + Tregs using probiotics or by in vitro or in vivo procedures are under investigation to treat autoimmunity [ 20 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD4+ and CD8+ T cells play central roles in the pathogenesis of LVV ( 75 , 76 ). Recent evidence suggests that Th1- and CD8-mediated inflammation may be less responsive to TCZ treatment, whereas the molecular signatures of Th17, Tfh, and Treg cells are improved.…”
Section: Discussionmentioning
confidence: 99%
“…PTRRC can play a pro-apoptotic and anti-apoptotic role by activating Akt through PI3K, and the activation of Akt signaling can inhibit a variety of pro-apoptotic factors. The rapamycin complex (mTOR) is located downstream of Akt, especially mTORC1 (part of mTOR) regulates the differentiation and function of effector T cells by integrating microenvironmental factors [21] . It has been reported that in GCA, mTORC1 is continuously active and provides energy for the development of GCA by synthesizing ATP through the glycolytic pathway [22] .…”
Section: Discussionmentioning
confidence: 99%